Ritual Kampua Bagi Orang Muna di Desa Waara Kecamatan Lohia Kabupaten Muna - Devianti, Devianti; Jers, La Ode Topo; Suraya, Rahmat Sewa (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
The purposes of this study were (1) to analyze the reasons for using goats as a complete custom in the Kampua ritual in Waara Village, Lohia District, Muna Regency. (2) To describe the meaning of goat slaughter in the Kampua ritual for muna people in Waara Village, Lohia District, Muna Regency. This study uses the theory of symbols from Geertz. The data collection technique is field research using ethnographic methods of involved observation and interviews. The data analysis technique used is descriptive qualitative.The results of the study show that (1) Kampua ritual for the Muna people is one of the most important religious rituals among the Muna people. So that the Muna people consider this ritual as a sacred ritual that has been passed down from their ancestors for generations. In the Kampua ritual, there is also the slaughter of goats, which is a hereditary tradition that is still maintained today and is carried out repeatedly. (2) The process of carrying out the Kampua ritual for muna people in Waara Village, Lohia District, Muna Regency has several stages, namely (a) Katununo incense (burning incense) (b) Kabasano Bharasandi (barsanji reading) (c) Kaalano Wulu (hair cutting) (d) ) katanda Wite (laying the ground) (e) Kabasano Haroa (reading the haroa prayer), the prayer is intended as one of the activities to ask for peace and comfort in the life of children in Kampua.